Federal union, modern world the law of nations in an age of revolutions, 1776-1814 - Onuf, Peter S. 1946-; Onuf, Nicholas Greenwood 1941- (Madison House, 1993)
In this thought-provoking analysis of international relations, the Onufs deepen our understanding of the ideas that forged the law of nations in a world of revolutions. Taking a time of extraordinary change as its frame of reference, Federal Union, Modern World relates the emergence of the modern concept of state-societies to the remarkable experiments in constitution-making in the United States. It shows how efforts to model a federal union in America influenced the broader relations of European nation-states. Relying on ancient and early modern sources prominent in the minds of the Founders, the authors demonstrate how the idea of a federal union was applied to the nations of the world. This profound paradigm shift in international relations divorced the law of nations from naturalism and grafted it onto modern ideas of liberalism. The formation of the United States as a federation, argue the Onufs, "expressed Enlightenment impulses . . . more fully than any contemporaneous developments in Europe." Furthermore, as the Founders attempted to secure a tenable position for their creation, they inspired a shift in international relations theory from natural legal doctrine to the positive law of states. This book is a contribution to the new history of "conceptual change," drawing selectively on the history of diplomacy, political theory, and legal doctrine to identify and relate some important themes in the emergence of the modern world. This relevant and timely study of international union and disunion informs us as much about the decades of revolution as it does about the context of international relations and federalism in our own time.
Keywords: Geschichte 1776-1814; Gouvernement fédéral - Etats-Unis - Histoire; Außenpolitik; Geschichte; Internationales Recht; Federal government -- History; International law -- History; Bundesstaaten; Völkerrecht; Etats-Unis - Relations extérieures - 1783-1815; USA; United States -- Foreign relations -- 1783-1815